Diseño de sistema automatizado para el aprovechamiento de lodos residuales en PTAR y PTAP de Veolia Tunja (2023)
In the degree work document presented below, an automated brick factory was designed to make bricks using as an input the residual sludges generated in the PTAP and PTAR treatment plants property of Veolia Aguas de Tunja S.A. E.S.P.